Quality Assurance Model using Lean Manufacturing and ERC Work Motivation to Reduce the Rate of Defective Production of a Footwear SME - Cuadros-Lopez, R. (2023)
Footwear imports have been increasing in recent years and have radically affected the profitability of the footwear sector, especially those from China. This situation has particularly affected SMEs in this sector, as they lack sophistication with respect to the quality of their products and the lack of quality assurance strategies. In Peru, SMEs represent a great importance for its economy, since approximately 99.5% of its companies are SMEs. Specifically, SMEs in the footwear sector generate 57,000 direct jobs and contribute 1.2% of the industrial GDP. Therefore, there is a need for research to ensure the quality of the footwear produced by SMEs in order to make them more competitive in the market. This through a model of quality assurance by combining the tools of quality standardization and motivation ERC. This is expected to reduce the rate of defective production of SMEs in the footwear sector in order to increase the sophistication of their products with respect to quality and generate an efficient and sustainable production.